2013
DOI: 10.1155/2013/831976
|View full text |Cite
|
Sign up to set email alerts
|

Three-Point Bending Tests of Zirconia Core/Veneer Ceramics for Dental Restorations

Abstract: Introduction. The mechanical strength and the surface hardness of commercially available yttrium-doped zirconia were investigated. Furthermore, a comparative study of eight different ceramic veneers, to be used for the production of two-layered all-ceramic restorative systems, was carried out. Materials and Methods. Four types of zirconia specimens were analyzed, according to a standard ISO procedure (ISO 6872). Besides, two-layered zirconia-veneer specimens were prepared for three-point bending tests. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 17 publications
0
50
0
1
Order By: Relevance
“…The case A shows a maximum stress slightly higher than that shown by the case B. In this outcome, it is important to evaluate the role of the geometry of the implants used, as well as the prosthesis chosen and integrated in the oral cavity (11,12). Moreover, the stress distribution on the mandibular ridge appears more uniform in case A, compared to the case B.…”
Section: Resultsmentioning
confidence: 95%
“…The case A shows a maximum stress slightly higher than that shown by the case B. In this outcome, it is important to evaluate the role of the geometry of the implants used, as well as the prosthesis chosen and integrated in the oral cavity (11,12). Moreover, the stress distribution on the mandibular ridge appears more uniform in case A, compared to the case B.…”
Section: Resultsmentioning
confidence: 95%
“…Animal experiments to elucidate the differences of CA coated Y-TZP at different heating conditions are needed in the near future. Moreover, Marrelli et al [23] reported that surface roughness of zirconia strongly affected the mechanical strengths. Change of the mechanical strengths of Y-TZP after CA coating should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the reported biomechanical tests seem to confirm that the biomaterials subjected to CAM milling processes retain their physic properties and the only alterations are due to errors in the design stage. 3 Therefore, the comparability between two or more materials is an important prerequisite to clearly define the characteristics of the investigated materials. In recent years, regenerative medicine issues have stimulated research to investigate an elevated number of new biomatrices 4 aimed at improving tissue healing; in this light, the old concept of bioscaffolds has given way to new concepts, such as acellular scaffolds, 5 cell niche, and cell commitment.…”
Section: Discussionmentioning
confidence: 99%